Deskripsi Kemampuan Siswa SMP dalam Menyelesaikan Soal Cerita Materi Aritmetika Sosial - Awi Dassa; Bernard; Andi Sriwahyuningsih (Issues in Mathematics Education (IMED), 2022)
This study aims to describe the ability of students in solving social arithmetic story problems. The type of research used is qualitative research with a descriptive approach. There are six research subjects, namely, two high-ability students, two moderately capable students, and two low-ability students. The data collection technique in this research is by doing a social arithmetic test. The instruments used in data collection were written tests and interviews. The results showed that subjects with high mathematical ability (SKT), were able to write known and asked correctly, were able to write formulas, and students were able to solve verbal problems. Subjects with moderate mathematical ability (SKS), are able to determine what is known and asked, but are less able to write formulas, and are unable to solve verbal problems. Subjects with low mathematical ability (SKR), unable to write well known and asked, unable to write formulas, and unable to solve verbal problems. The results of this study are expected to add insight and improve students' abilities in solving math story problems related to the application of everyday life.